Peranan hukum Tua dalam mewujudkan Transparansi dan Akuntanbilitas Pembangunan Desa Seretan Kecamatan Lembean Timur Kabupaten Minahasa - Saumana, Nigel; Posumah, Johnny Hanny; Pombengi, Jericho Denga (Sam Ratulangi University, 2015)
ABSTARCT: The authority of leadership village leader as Hukum Tua in Minahasa Regency, is head the legal community unity which has borders authorized to regulate and manage the affairs of government, the interests of the local community by community initiatives, the right of origin, and / or traditional rights are recognized and respected in the system of government of the Republic of Indonesia. Good Governance be a good idea in order to improve the quality of public services that the village government organized jointly between the Hukum Tua, BPD, community organizations and the public with the principles of transparency and accountability. Therefore, this study aims to determine the role of the Hukum Tua in realizing the transparency and accountability of development in the village of East Lembean drag troughs District of Minahasa.The research proves that the role of the Hukum Tua in realizing the principle of transparency in village drag troughs are good, because the ability to convey information and financial development programs are often delivered village itself directly to the community and village, in meetings or in the event of joy and sorrow. Communication patterns often hold a general meeting every three (3) months and provide information boards so people can determine the extent of the activities that have and have not done. The principle of accountability also good because the Hukum Tua in delivering accountability of the duties and obligations is delivered directly to the public through a loudspeaker as well as the accountability report (LPJ) be submitted in writing to the BPD, Head and forwarded to the Regent Minahasa, in determining the commitment to the process of delivering LPJ BPD and there is conformity with the vision and mission of the village government.The method used in this study is a qualitative study with 32 informants. It can be concluded that the role of Hukum Tua villages Seretan troughs in accountable is the transparency to stakeholders received good appreciation by almost all members of the Rural Colusion Organization receives accountability report Hukum Tua. Considered appropriate for a person of honor calls Ukung Tu'a is Tu'a in walak. Hukum Tua (Rural Head) can be interpreted as a protector.Key words: The role Hukum Tua, Transparency, Accountability, Rural Development